Feasibility of simultaneous 18F-FDG PET/MRI for the quantitative volumetric and metabolic measurements of abdominal fat tissues using fat segmentation. Issue 6 (June 2016) - Im, Hyung-Jun; Paeng, Jin Chul; Cheon, Gi Jeong; Kim, Euishin E.; Lee, Jae Sung; Goo, Jin Mo; Kang, Keon Wook; Chung, June-Key; Lee, Dong Soo
Abstract : Background: Quantification of volume and inflammatory activity in the fat tissue is important because these are closely related to type 2 diabetes mellitus and cardiovascular disease. Fluorine-18 fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) has been utilized to measure the metabolic activity of fat tissue. In this study, we assessed the feasibility of simultaneous PET/magnetic resonance (MR) in metabolic and volumetric measurements of fat tissue and the potential advantage over PET/CT. Methods: Twenty-four healthy individuals were enrolled, who underwent simultaneous 18 F-FDG PET/MRI. Twenty-five 18 F-FDG PET/CT scans were selected. Isocontour volumes of interest (VOIs) were used to segment and separate visceral fat (VF) and abdominal subcutaneous fat (SF) in using the MR image (T1 DIXON VIBE sequence) of PET/MR and the CT image of PET/CT. Volume, mean standardized uptake value of VF, and SF VOIs were calculated. Results: Overlap between 18 F-FDG PET and VF VOI was better in 18 F-FDG PET/MR than PET/CT. The mean standardized uptake value of VF was associated with the degree of intestinal uptake on 18 F-FDG PET/CT, but not on 18 F-FDG PET/MR. Volumetric and metabolic measurements using 18 F-FDG PET/MR showed an excellent reproducibility, with a high intraclass correlation coefficient between different observers (0.951–0.997). The measured metabolic activity was higher in VF than SF. Conclusion: We established a method for the quantitative measurement of volume and metabolic status of abdominal VF and SF using simultaneous 18 F-FDG PET/MR. 18 F-FDG PET/MR has an advantage over 18 F-FDG PET/CT in terms of being less confounded by intestinal uptake. This method could be used to assess the inflammatory activity of fat tissue, which is a major risk factor for type 2 diabetes mellitus and cardiovascular disease.